Innovative Approaches Towards the Formation of Contractual Terms within the Effective System of Risk Management in Foreign Economic Activities - Vladimirovna Maslennikova, Natalia; Viktorovich Kravchenko, Aleksandr; Abdulxamidovich Orazaliev, Artur; Valentinovna Yakubova, Ella; Vladimirovna Slavnetskova, Ludmila (International Journal of Engineering and Technology, 2018)
The category of contractual risk is considered, which enables to effectively manage activity on the product market in the conditions of scenario uncertainty as well as to evaluate economic feasibility of legal constructions and means of the legal arsenal. In the article the importance of the system risk management in carrying out foreign economic activity is justified. The classification of risks in foreign trade is related consistently and in details. The analysis of innovative approaches towards the formation of contractual terms within the effective system of risk management is of particular interest. Incoterms 2010 was selected as a founding document in contractual terms, thus, a detailed practice of the choice of appropriate basic terms of delivery is presented. A structure of foreign trade prices and factors affecting it are provided for the justification of the selected terms. At the modern stage a system of risk management allows ensuring not only national security of the state but also enables to establish partnership relations with the participants of foreign trade activity that are based on the principle of categorizing, in accordance with which an automatic technology of categorizing the participants of foreign trade activity is developed.Â Â
Keywords: a system of risk management; contractual terms; foreign trade activity; delivery terms; Incoterms 2010